The Effect of Market Orientation and Product Innovation on Performance-Mediated Competitive Advantage Marketing(Case Study of MSME Boutiq Women in Medan Market Center) - satria Tirtayasa; Hery Syahrial; Nasib; Beby Nofriza (TRIGIN PUBLISHER, 2022)
The purpose of this study was to examine the role of market orientation and product innovation on competitive advantage mediated by marketing performance on women's Boutiq SMEs in the market center. The quantitative associative methodology is used in this study. All fashion SMEs in the market center of Medan is the population in this study. The sample used is 120 respondents. Questionnaires and interviews that have been tested for validity and reliability are data collection techniques used. The data analysis used in this research are (1) structural model analysis (inner model), (2) reliability test (3) variance extract). The results of the study show that (1) the effect of market orientation on competitive advantage with a value of 4.185 is significantly positive. (2) market product innovation towards a competitive advantage with a value of 2.771 is significantly positive. (3) product competitive advantage on marketing performance with a value of 5.275, is positive and significant. (4) product innovation in mediating market marketing performance on marketing performance with a value of 6.334 is considered positively significant (5) market orientation towards a competitive advantage with a value of 6.360 is significantly positive. (6) the effect of competitive advantage on marketing performance with a value of 7.035 is positively significant. (7) the effect of product innovation on competitive advantage with a value of 6.334 is a significant positive.